2017
DOI: 10.1038/s41598-017-08292-4
|View full text |Cite
|
Sign up to set email alerts
|

Sleep mediates the association between homocysteine and oxidative status in mild cognitive impairment

Abstract: Tremendous progress has been made over the last few years in understanding how sleep and amyloid-β (Aβ) cooperate to speed up the progression of Alzheimer’s disease (AD). However, it remains unknown whether sleep deficits also interact with other risk factors that exacerbate the pathological cascade of AD. Based on evidence showing that higher levels of homocysteine (HCY) and sleep loss increase oxidative damage, we here investigate whether the relationship between HCY and total antioxidant capacity (TAC) is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
(58 reference statements)
2
15
0
Order By: Relevance
“…Consequently, lower intake of these B vitamins and elevated serum Hcy level are linked to altered DNA methylation patterns, which has been observed in AD patients [18]. As a neurotoxin, an increased level of Hcy has also been shown to affect redox signaling pathways in neurons by generating reactive oxygen species (ROS) and decreasing endogenous antioxidants [19]. It is therefore of interest to see whether DNA methylation patterns in redox-related genes could modulate cognitive impairment conferred by B vitamin deficiency and hyperhomocysteinemia.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, lower intake of these B vitamins and elevated serum Hcy level are linked to altered DNA methylation patterns, which has been observed in AD patients [18]. As a neurotoxin, an increased level of Hcy has also been shown to affect redox signaling pathways in neurons by generating reactive oxygen species (ROS) and decreasing endogenous antioxidants [19]. It is therefore of interest to see whether DNA methylation patterns in redox-related genes could modulate cognitive impairment conferred by B vitamin deficiency and hyperhomocysteinemia.…”
Section: Introductionmentioning
confidence: 99%
“…Another study investigated 21 healthy older adults and 21 individuals with mild cognitive impairment and found that shorter sleep duration may contribute to elevated homocysteine levels and oxidative stress. 24 The other animal study found that sleep deprivation may reduce rather than enhance homocysteine levels in rats. 25 However, no related evidence was collected in human studies.…”
Section: Discussionmentioning
confidence: 97%
“…Few studies examined the association between TAC and cognitive impairment in older adults. For instance, one study has suggested that lower level of TAC was independently correlated with less grey matter in the middle temporal lobe in patients with mild cognitive impairment 65 . Another study supported this finding, revealing a considerably lower brain metabolic rate in the inferior and temporal lobes of patients with weak cognitive function when compared to a matched healthy group 66 .…”
Section: Discussionmentioning
confidence: 99%